JOB CRAFTING MEMEDIASI PENGARUH JOB DEMANDS DAN LEARNING GOAL ORIENTATION TERHADAP WORK ENGAGEMENT PADA KARYAWAN PT. SANDABI INDAH LESTARI BENGKULU UTARA - Novianti, Nova Novianti (Managament Insight: Jurnal Ilmiah Manajemen, 2025)
The purpose of this study was to test whether job demands and orientation of learning objectives had an effect on work engagement at PT Sandabi Indah Lestari Bengkulu Utara. In addition, this study was used to test whether learning goal orientation had an effect on work engagement mediated by job crafting at PT Sandabi Indah Lestari Bengkulu Utara. The type of research used is quantitative research, where there is hypothesis testing. The data collection method is by distributing online questionnaires through a hand delivery survey. The population in this study were employees who worked at the Bengkulu Province Public Works and Spatial Planning Office. This study has 43 questions given to the respondents. The number of respondents in this study that was processed was 242 respondents. The analysis in this study uses SmartPLS. The results of this study explain that: (1) job demands affect job involvement, (2) learning goal orientation affects job involvement, (3) job demands affect work craft, (4) learning goal orientation affects work craft, (5) work craft affects work job involvement, (1) job demands affect mediated job involvement. by job crafting and (7) the orientation of learning objectives affects work engagement mediated by job crafting. Keywords: learning goal orientation, job demands, , job crafting, work engagement.